Extensive Deep Venous Thrombosis in a Patient with Interleukin-36 Receptor Antagonist Deficiency (DITRA): A Case Report - ACVD, Espíndola; FMS, Casimiro; JB, Pesquero; RF, Magalhães (Archives of Clinical and Medical Case Reports, 2019)
Abstract not available in the source database.